The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.2478/zireb-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Contraction of European Economic Distances through Sustainable Tourism in the Pre-Pandemic Period

Abstract: The current importance of tourism leads us to analyze the extent to which the receipts from international tourism, and tourism in general, influence the capacity of European countries to reduce the development gaps of this sector in the European context and the extent to which the economic growth is sensitive to changes in tourist arrivals, tourism receipts and expenditures. Studying the GDP per capita and the receipts from international tourism for the period 1995-2017, we find that the European tourism has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The impact of tourism can be measured by means of tourism receipts, but tourism expenditures [ 32 , 33 ] and the number of arrivals [ 4 ] are equally important. Analyzing how sustainable tourism helps reduce inequalities between European states, Haller (2021) [ 34 ] showed that international tourism expenditures, receipts and, to a lesser extent, tourist arrivals contribute to narrowing development gaps, emphasizing the importance of sustainable tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of tourism can be measured by means of tourism receipts, but tourism expenditures [ 32 , 33 ] and the number of arrivals [ 4 ] are equally important. Analyzing how sustainable tourism helps reduce inequalities between European states, Haller (2021) [ 34 ] showed that international tourism expenditures, receipts and, to a lesser extent, tourist arrivals contribute to narrowing development gaps, emphasizing the importance of sustainable tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The paper also compared the market efficiency status and January effect status between the two markets (emerging and industrial markets). A country is said to have an emerging market if it is improving its economy to become more advanced [ 30 ]. An industrial market is that of a country with matured economy and evenly distributed economic level [ 31 ].…”
Section: Introductionmentioning
confidence: 99%